Implementation of Microphone Electronic Media to Increase Confidence in Children 4-5 Years Old at PG-TK Panca Budi Medan - Fadilla Yana Maulia; Asmidar Parapat; Mhd Habiburahman (Yayasan Multidimensi Kreatif, 2025)
This research aims to increase the confidence of children aged 4-5 years through the implementation of microphone electronic media. This research is qualitative with data collection through observation, interview, and documentation methods. The subjects of this study were 30 children, consisting of 13 boys and 17 girls. The results of the study show that the implementation of microphone electronic media significantly increases children's self-confidence. Most of the children showed positive development in the courage to appear in front of the class, dare to express their opinions, and be enthusiastic in participating in activities. However, there are 5 children who still show a lack of confidence, because children are not used to showing their potential so that children feel afraid and embarrassed when raising their voices in front of many people.